Like a Loaded Weapon : The Rehnquist Court, Indian Rights, and the Legal History of Racism in America - Williams, Robert A., Jr., 1955- (Book collections on Project MUSE., 2005)
Robert A. Williams, Jr., boldly exposes the ongoing legal force of the racist language directed at Indians in American society. Building on the insights of Malcolm X, Thurgood Marshall, and Frantz Fanon, Williams argues that racist language has been employed by the courts to legalize a uniquely American form of racial dictatorship over Indian tribes by the U.S. government.